Awake Fiberoptic Intubation Protocols in the Operating Room for Anticipated Difficult Airway: A Systematic Review and Meta-analysis of Randomized Controlled Trials. (May 2019) - Cabrini, Luca; Baiardo Redaelli, M; Ball, Lorenzo; Filippini, Martina; Fominskiy, Evgeny; Pintaudi, Margherita; Putzu, Alessandro; Votta, Carmine D.; Sorbello, Massimiliano; Antonelli, Massimo; Landoni, Giovanni; Pelosi, Paolo; et al.
Abstract : Awake fiberoptic intubation is one of the recommended strategies for surgical patients with anticipated difficult airway, especially when concurrent difficult ventilation is expected. We performed the first systematic review of randomized controlled trials assessing different protocols for awake fiberoptic intubation in anticipated difficult airway, including studies investigating elective awake fiberoptic intubation for scheduled surgery; randomized controlled trials comparing different methods for performing awake fiberoptic intubation; and adult patients with anticipated difficult airway. We excluded studies in the nonoperating theater settings, randomized controlled trials comparing awake fiberoptic intubation with other techniques, and studies based on simulation. Primary outcomes were success rate and death; secondary outcomes were major adverse events. Thirty-seven randomized controlled trials evaluating 2045 patients and 4 areas were identified: premedication, local anesthesia, sedation, and ancillary techniques to facilitate awake fiberoptic intubation. Quality of evidence was moderate–low and based on small-sampled randomized controlled trials. Overall, 12 of 2045 intubation failures (0.59%) and 7 of 2045 severe adverse events (0.34%) occurred, with no permanent consequences or death. All evaluated methods to achieve local anesthesia performed similarly well. No differences were observed in success rate with different sedatives. Dexmedetomidine resulted in fewer desaturation episodes compared to propofol and opioids with or without midazolam (relative risk, 0.51 [95% CI, 0.28–0.95]; P = .03); occurrence of desaturation was similar with remifentanil versus propofol, while incidence of apnoea was lower with sevoflurane versus propofol (relative risk, 0.43 [95% CI, 0.22–0.81]; P = .01). A high degree of efficacy and safety was observed with minimal differences among different protocols; dexmedetomidine might offer a better safety profile compared to other sedatives.